PENERAPAN MANAJEMEN KRISIS DI INDONESIA : MEMOTRET KRISIS DALAM KACAMATA PUBLIC RELATIONS - Luhukay, Marsefio S. (Scriptura, 2008)
Public relations as a proactive management function, which performs the effort of monitoring trends, events, issues that may arise and distract the important relationships in a company. The continuous monitoring effort done by the Public Relations through informal relationship, and others, may give big benefit to the company when the crisis occurs. That’s why, PR can be said to be the portrait of the company. It is the eyes, ears and at the same time, the speaker for the organization. When an organization trembles, PR stands forward, when organization at a stable condition, it remains diligent in research and analysis, when a company moves forward, it stands behind, supports all organization’s supporting activity and programs. In other words, Public Relations is a must. When a crisis occurs, PR exists as a facilitator and mediator between organization and it’s public. That’s why I emphasized in my preamble’s argumentation that PR is highly needed in an organization, especially in Indonesia which, from my point of view, still gives meaning and locates PR in a highly different position as it is supposed to be.